(untitled) (Ocean and Coastal Research, 2021)
Several ecosystem processes and services provided by mangrove trees, such as the regulation of biogeochemical cycles, biological control, soil retention and protection against erosion, and especially CO2 assimilation and carbon storage are related to the photosynthetic process (Donato et al. 2011; Schaeffer-Novelli et al., 2016; Santos et al., 2017). Photosynthesis is directly related to chlorophyll present in the leaves, and assessment of chlorophyll concentrations may be used as an indicator of a plants’ physiological condition. Decreases in leaf chlorophyll concentrations occur in plants exposed to environmental stress, including stress caused by heavy metals (Chandra & Kang, 2016), nutrient deficiency (Kalaji et al., 2017), and petroleum pollution (Arellano et al., 2017), among others. Thus, estimates of chlorophyll concentrations may provide information on plant and ecosystem function (Heenkenda et al., 2015; Pastor-Guzman et al., 2015).